The efficacy and safety of MARS-PD: Meridian activation remedy system for Parkinson's disease-A single-center, assessor and statistician-blinded, parallel-group randomized, controlled trial protocol. - Miso S Park; SangSoo Park; Jie-Yoon Kang; In Chul Jung; HoRyong Yoo (PLoS ONE)
Background Parkinson's disease (PD) patients face a substantial unmet need for disease-modifying interventions. Potential approaches such as exercise and acupuncture have been investigated to slow PD progression. To address this unmet need, we developed a novel therapeutic approach that integrates acupuncture and exercise: the Meridian Activation Remedy System for PD patients (MARS-PD). Building upon promising outcomes observed in our preliminary pilot study, where MARS-PD exhibited a large clinically important difference on the Movement Disorder Society Unified Parkinson's Disease Rating Scale Part III (MDS-UPDRS Part III), we embark on a randomized controlled trial with the primary objective of examining the efficacy, safety, and economic impact of MARS-PD. Methods In this single-center, assessor and statistician-blinded, parallel-group randomized controlled trial, we aim to investigate the clinical efficacy of MARS-PD through 16 interventions administered over 8 weeks in 88 PD patients. Participants will be randomly assigned to the experimental (n = 44) or control (n = 44) groups. The experimental group will receive MARS-PD intervention alongside standard care, while the control group will solely receive standard care. The intervention period spans 8 weeks, followed by a 12-week post-intervention follow-up. The primary endpoint is the change in MDS-UPDRS Part III score from baseline to the conclusion of the 8-week intervention. Secondary outcomes encompass various assessments, including MDS-UPDRS, International Physical Activity Questionnaire Short Form, Parkinson Self Questionnaire, Parkinson's Disease Sleep Scale, Timed Up and Go test, GAITRite metrics, Functional Near-Infrared Spectroscopy measurements, smart band outcomes, gut microbiome analysis results, and iris connective tissue texture. Discussion Previous studies by the authors have indicated MARS-PD's safety and benefits for PD patients. Building upon this foundation, our current study aims to provide a more comprehensive and detailed confirmation of the efficacy of MARS-PD. Trial registration cris.nih.go.kr KCT0006646 -First posted on 7 October 2021; ClinicalTrials.gov NCT05621772 -First posted on 11 November 2022.